Carbon‐film‐based Zernike phase plates with smooth thickness gradient for phase‐contrast transmission electron microscopy with reduced fringing artefacts. (4th May 2022) - Obermair, M.; Hettler, S.; Dries, M.; Hugenschmidt, M.; Spiecker, R.; Gerthsen, D.
Abstract: Phase plates (PPs) in transmission electron microscopy (TEM) improve the contrast of weakly scattering objects under in‐focus imaging conditions. A well‐established PP type is the Zernike (Z)PP, which consists of a thin amorphous carbon (aC) film with a microscaled hole in the centre. The mean inner potential of the aC film is exploited to shift the phase of the scattered electrons while the unscattered electrons in the zero‐order beam propagate through the hole and remain unaffected. However, the abrupt thickness increase at the hole edge induces an abrupt change of the phase‐shift distribution and leads to fringing, that is, intensity oscillations around imaged objects, in TEM images. In this work, we have used focused‐ion‐beam milling to fabricate ZPPs with abrupt and graded thickness profiles around the centre hole. Depending on the thickness gradient and inner hole radius, graded‐ZPP‐TEM images of an aC/vacuum interface and bundles of carbon nanotubes (CNTs) show strongly reduced fringing. Image simulations were performed with ZPP‐phase‐shift distributions derived from measured thickness profiles of graded ZPPs, which show good agreement with the experimental images. Fringing artefacts, that is, intensity oscillations around imaged objects, are strongly reduced for Zernike phase plates with a graded thickness profile around the centre hole. Focused‐ion‐beam milling is used to fabricate graded Zernike phase plates with specific inner hole radius and thickness gradients. The phase‐shift distribution is obtained from measured thickness profiles around the centre hole. Image simulations based on experimentally measured thickness/phase‐shift distributions show good agreement with experimental Zernike phase‐plate TEM images.